2000
DOI: 10.1149/1.1393469
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Treated InP(100) Surfaces in Aqueous HCl Solutions

Abstract: Cleaning and passivation of semiconductor surfaces are of great importance in crystal growth and device fabrication. Several cleaning procedures are available for InP wafers, for example, chemical cleaning, 1,2 thermal cleaning, 3-5 and atomic hydrogen irradiation. 6,7 Among them, the chemical cleaning is the simplest and easiest to control.Unlike Si which forms a very excellent interface with its oxide, SiO 2 , the native oxide of InP is detrimental due to the formation of surface traps and interface states a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
1
25
3
Order By: Relevance
“…It is also shown that the HCl-and HF-treated GaAs and InP surfaces are hydrophobic. 2,3,8,12 These results are in direct contrast to those obtained on alkaline etched GaP and GaAs surfaces ͑i.e., hydrophilic͒. The inset in Fig.…”
Section: Wettabilitycontrasting
confidence: 67%
See 2 more Smart Citations
“…It is also shown that the HCl-and HF-treated GaAs and InP surfaces are hydrophobic. 2,3,8,12 These results are in direct contrast to those obtained on alkaline etched GaP and GaAs surfaces ͑i.e., hydrophilic͒. The inset in Fig.…”
Section: Wettabilitycontrasting
confidence: 67%
“…An increase in the roughened overlayer thickness with increasing immersion time t in HCl was observed on GaP͑111͒, GaAs͑001͒, and InP͑001͒ surfaces. 2,12,27 In contrast, no clear degradation of the chemically treated surfaces was observed on alkaline etched GaAs͑001͒ in NH 4 OH, KOH, and NaOH solutions. 21 …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…2, 3,9,14 These results are in direct contrast to those obtained on alkaline-etched GaP͑001͒ surfaces ͑i.e., hydrophilic͒. The inset in Fig.…”
Section: Wettabilitycontrasting
confidence: 59%
“…1-3 Among them, chemical cleaning is the simplest and easiest to control and has been widely applied to GaAs, 2-13 InP, 3,11,[14][15][16] and GaP. 17,18 The chemicals used in these studies are mainly acidic ͑HCl, HF, H 2 SO 4 /H 2 O 2 , etc.͒ and alkaline ͑KOH, NH 4 OH, etc.͒ solutions.…”
Section: Introductionmentioning
confidence: 99%